If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the first equation is substituted into the second equation.

−x + 5y = 1
2x + 4y = −4
2(5y − 1) + 4y = −4
2(−5y + 1) + 4y = −4
2x + 4(−5y + 1) = −4
2x + 4(5y − 1) = −4

Respuesta :

mergl
-x+5y=1
2x+4y=-4
5y-1=x

=2(5y-1)+4y=-4

Answer:

2(5y-1) + 4y = −4

Step-by-step explanation:

−x + 5y = 1   ----------> first equation

2x + 4y = −4  ---------> second equation

we solve the first equation for x

−x + 5y = 1

To solve for x we need to get 'x' alone

Add x on both sides

5y = 1+x

Now subtract 1 from both sides

x= 5y - 1

Plug in 5y-1 for x in the second equation

2x + 4y = −4

2(5y-1) + 4y = −4

ACCESS MORE